2016
DOI: 10.1016/j.jadohealth.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Non-Nucleoside Reverse Transcriptase Inhibitor–Based Antiretroviral Therapy in Perinatally HIV-Infected, Treatment-Naïve Adolescents in Asia

Abstract: Purpose About a third of untreated, perinatally HIV-infected children reach adolescence. We evaluated the durability and effectiveness of non-nucleoside reverse transcriptase inhibitor (NNRTI)-based antiretroviral therapy (ART) in this population. Methods Data from perinatally HIV-infected, antiretroviral-naïve patients initiated on NNRTI-based ART aged 10–19 years who had ≥6 months of follow-up were analyzed. Competing risk regression was used to assess predictors of NNRTI substitution and clinical failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…After a median of seven years of ART, ALWHIV could still be on a successful first-line regimen in RLS like Cameroon. With the median age of 13 years in a population apparently asymptomatic, these findings also demonstrate the benefits of ART amongst ALWHIV, and advocate for strategies toward improved management [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 91%
“…After a median of seven years of ART, ALWHIV could still be on a successful first-line regimen in RLS like Cameroon. With the median age of 13 years in a population apparently asymptomatic, these findings also demonstrate the benefits of ART amongst ALWHIV, and advocate for strategies toward improved management [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 91%
“…A study done on comparison between NVP and lopinavir-ritonavir [ 36 ] was excluded as it was not the interest of this review. Other six papers were excluded as the studies were conducted among children [ 37 ], conducted outside of sub-Saharan Africa, [ 38 , 39 , 40 , 41 ], and systematic reviews and meta-analysis articles [ 20 ] were. Subsequently, of 79 full record articles, a total of 36 were eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Substantial increases in WAZ at ART initiation over time were observed among children in Central Africa, with mean z-scores increasing from −2.2 in 2004–2005 to −1.4 in 2012–2013 [24]; the percent underweight decreased from 56% to 36% over this period. However, it should be noted that younger children (<10 years) comprise the majority of the populations in the studies described above, and several studies which report growth measures specifically for adolescents (age 10–19) have identified more severe growth deficits than among younger children [17,19].…”
Section: Adolescent Growth Measures Prior To Art Initiationmentioning
confidence: 99%
“…Among Chinese HIV-infected youth, a 2-year increase of about 0.4 in both HAZ and WAZ was observed, with corresponding decreases in prevalence of stunting from 42% to 34% and in underweight from 21% to 13% [18]. After 5 years on ART, adolescents in the TREAT Asia Pediatric HIV Observational Database (TApHOD) achieved increases in HAZ from −2.3 to −1.6 [17]. Similar improvement was observed in both HAZ and WAZ by 4 years after ART initiation among South African and West African youth [12] (see Table 2).…”
Section: Growth In Hiv-infected Adolescents After Art Initiationmentioning
confidence: 99%
See 1 more Smart Citation